A comparative linguistic analysis of English news headlines in China, USA, UK, and ASEAN countries. (24th November 2020) - Zhang, Yusha; Lu, Xiaoming; Fu, Yingwen; Jiang, Shengyi
This paper aims to conduct a comparative study on English news headlines in the USA, China, the UK, and ASEAN countries, mainly investigating how the composing of news headlines is interrelated with its linguistic factors such as the part of speech, length and the frequency of most common words depending on which country the news is published in. In this paper, the linguistic comparison is performed based on merely the headlines without going through whole articles. For this purpose, 13 sets of data are collected from major online news sites within above-mentioned countries. The comparison results reveal that headlines in different countries comply with news writing rules in slightly different ways as well as boast distinctive features. These differences are attributed to the consideration of the target audience's multi-faceted states such as knowledge states, beliefs, or interests. To better exemplify the results, the headlines in this article were read with care. The proposed method begins with data collection and pre-processing. News headlines are then fetched from different news sources using crawler and processed in natural language processing tool (NLTK).